2014
DOI: 10.21273/horttech.24.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Yellow Squash Using Sequential Postdirected Applications of Pelargonic Acid

Abstract: Squash (Cucurbita pepo) producers could benefit from additional herbicide options that are safe to the crop and provide effective weed control. Research was conducted in southeastern Oklahoma (Atoka County, Lane, OK) during 2010 and 2011 to determine the impact of pelargonic acid (PA) on weed control efficacy, crop injury, and squash yields. The experiment included PA applied unshielded postdirected at 5, 10, and 15 lb/acre, plus an untreated weedy control and an untreated we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Arboleya et al (2005) found pelargonic acid to have desiccant properties in onion production, although other herbicides were more effective. Pelargonic acid effectively controlled weeds in squash (Cucurbita pepo) when applied with a precision directed sprayer (Webber et al, 2014).…”
mentioning
confidence: 99%
“…Arboleya et al (2005) found pelargonic acid to have desiccant properties in onion production, although other herbicides were more effective. Pelargonic acid effectively controlled weeds in squash (Cucurbita pepo) when applied with a precision directed sprayer (Webber et al, 2014).…”
mentioning
confidence: 99%
“…Nonanoic acid was not effective in controlling weeds probably because the species in these experiments were too developed for the herbicide to have an effect. Previous research reported that nonanoic acid needs to be applied to very young or small plants for acceptable weed control [36], and repeated applications are suggested [8]. Rowley et al [37] obtained a moderate reduction in weed coverage, density, and dry biomass compared to the untreated control, but the dose of nonanoic acid used (39 L a.i.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative methods to the use of chemical-synthesis herbicides are alternative organic herbicides and thermal weed control [3,8,9]. Nonanoic acid (also called pelargonic acid) is a contact, non-selective, non-translocating, post-emergence non-synthetic herbicide [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations